2020
DOI: 10.1371/journal.pone.0230105
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Prevalence in South Africa by settlement type: A repeat population-based cross-sectional analysis of men and women

Abstract: To assess i) whether there is an independent association between HIV-prevalence and settlement types (urban formal, urban informal, rural formal, rural informal), and, ii) whether this changes over time, in South Africa. We draw on four (2002; 2005; 2008; 2012) cross-sectional South African household surveys. Data is analysed by sex (male/female), and for women by age categories (15-49; and 15-24; 25-49) at all-time points, for men in 2012 data is analysed by age categories (15-24; 25-49). By settlement type a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 20 publications
1
23
0
9
Order By: Relevance
“…The national HIV prevalence for Zambia has generally been highest in urban areas (13,35,39) and this is similar to other countries within the region such as Malawi, Kenya, South Africa and Zimbabwe (40)(41)(42)(43). However, district level estimates from our study have revealed that HIV prevalence in some rural districts is comparable and sometimes even higher than the prevalence in urban districts.…”
Section: Discussionsupporting
confidence: 82%
“…The national HIV prevalence for Zambia has generally been highest in urban areas (13,35,39) and this is similar to other countries within the region such as Malawi, Kenya, South Africa and Zimbabwe (40)(41)(42)(43). However, district level estimates from our study have revealed that HIV prevalence in some rural districts is comparable and sometimes even higher than the prevalence in urban districts.…”
Section: Discussionsupporting
confidence: 82%
“…It is necessary to investigate what commonalities and differences in the health status of slum dwellers exist [ 20 ]. This refers both to the differences within a city between groups living in formal and informal settlements [ 24 ], which was done for HIV in South Africa [ 25 ], and to the differences across slums in different global regions. The aim here is to become aware of cultural, economic, geographical, infrastructural, religious, or other circumstances, their influences on the health of occupants, and the associated allocation to risk groups.…”
Section: What We Should Knowmentioning
confidence: 99%
“…Human Immunode ciency Virus has been described as a disease of poverty [11][12][13][14][15]28] , a variable that is used to allocate CHWs. If CHWs are under allocated in relation to PLWH, this may mean that the CHWs are not reaching the targeted poor individuals in the province.…”
Section: Discussionmentioning
confidence: 99%
“…Human Immunode ciency Virus is one of the infectious diseases of poverty [11] . Poverty has a complex association with HIV as shown in South African and other international studies [12][13][14][15] . KwaZulu-Natal is the third poorest province in South Africa, with communities in the rural areas having particularly high levels of poverty [7,16] which have been associated with high HIV prevalence [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 89%